Impact of air pollution and genotype variability on DNA damage in Prague policemen - Novotna, Bozena; Topinka, Jan; Solansky, Ivo; Chvatalova, Irena; Lnenickova, Zdena; Sram, Radim J (Toxicology letters, 2007)
DNA integrity was analyzed in the lymphocytes of 65 non-smoking city policemen during January and September 2004 using the comet assay combined with excision repair enzymes. Information about inhalation exposure was obtained by (1) stationary monitoring of PM2.5 and carcinogenic polycyclic aromatic hydrocarbons (cPAHs) during the sampling periods and (2) personal exposure monitoring of cPAHs 48h before blood sampling. The data were completed by a lifestyle questionnaire. Regardless of the season of the year, policemen working outdoors (exposed group) exhibited higher levels of DNA damage than those working indoors (controls). Within the exposed group, the levels of both unspecified and oxidative DNA damage detected in January significantly exceeded those found in September. The controls did not show analogous inter-seasonal variability. The winter levels of oxidative DNA damage positively correlated with exposure to cPAHs, probably reflecting increased oxidative stress as a result of high concentrations of PM2.5. In comparison with the wild type genotype, the carriers of at least one mutated allele, CYP1A1*2C (Ile/Val), MTHFR 2656 or MS 2656, and the EPHX1-medium phenotype appeared to be more susceptible specifically to the induction of oxidative DNA damage, while the p53 MspI mutation predisposed the carrier to a higher incidence of both breaks and oxidative lesions in DNA. In contrast, GSTM1-null and vitamin C tended rather to protect DNA integrity.
Keywords: methylentetrahydrofolátreduktasa (NADPH2); polycyklické aromatické uhlovodíky; Occupational Exposure; Oxidative Stress; Surveys and Questionnaires; oxidační stres; pevné částice; Cytochrome P-450 CYP1A1; Humans; Case-Control Studies; cytochrom P-450 CYP1A1; Lymphocytes; Methylenetetrahydrofolate Reductase (NADPH2); lymfocyty; polymorfismus genetický; studie případů a kontrol; Environmental Monitoring; dospělí; Carcinogens, Environmental; Genotype; lidé; Polycyclic Aromatic Hydrocarbons; Epoxide Hydrolases; Polymorphism, Genetic; průzkumy a dotazníky; Particulate Matter; policie; Adult; monitorování životního prostředí; karcinogeny životního prostředí; Comet Assay; roční období; pracovní expozice; epoxid hydrolasy; Seasons; Czech Republic; poškození DNA; DNA Damage; genotyp; kometový test; Česká republika; Police